Answer:
D
Step-by-step explanation:
First, find the slope using the slope formula. The slope is 3.
Now plug in any of the x and y values and the value of the slope into the slope-intercept form equation to solve for b.
9=3(3)+b, solve for b
b=0, Now convert the equation y=3x into slope-intercept form.
y-9=3(x-3) This is the equation of the line, the plant will be about 36 cm tall after 12 months.
If $125 is invested at an interest rate of 18% per year and is compounded continuously, how much will the investment be worth in 2 years? Use the continuous compound interest formula A=Pe^rt
Answer:
$179.17
Step-by-step explanation:
https://brainly.com/question/12714871
Answer: The investment be worth $ 174.05 in 2 years .
Step-by-step explanation:
Given : The principal amount invested : A= $125
Interest rate : r = 18% =0.18 [ Percent convert into decimal if we divide it by 100]
Time : t = 2 years
The formula to find the accumulated amount if compounded continuously :-
[tex]A=Pe^rt\\\\=(125)(1+0.18)^{2}\\\\= 125 (1.18)^2\\\\ = 125 (1.3924)\\\\=174.05[/tex]
Hence, the investment be worth $ 174.05 in 2 years .
The phosphate groups that are the polar of the phospholipid because they are A.charged B. Neutral C. Hydrophilic D. hydrophobic
Answer:
The phosphate groups that are the polar of the phospholipid because they are charged - A.
The phosphate groups that are the polar of the phospholipid because they are A. charged
What is phospholipid?It is group of polar lipids that consist of two fatty acids , a glycerol unit and a phosphate group .
A phosphate group has a negatively charged oxygen and a positively charged nitrogen to make this group ionic. A single phospholipid molecule has a phosphate group on one end and two chains of fatty acids . The phosphate group is negatively charged making the head polar and hydrophilic .
correct answer A) charged
learn more about phospholipid
https://brainly.com/app/ask?q=phospholipid
#SPJ2
PLEASE ANSWER FIRST GETS BRAINLIEST!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Let Bikes = B and cars = c
a bike has 2 wheels and a car has 4 wheels.
Equation 1: add bikes and cars to get total students:
b + c = 80
Equation 2: multiply the number of wheels by each type and add to equal the total wheels.
2b +4c = 270
Rewrite the first equation as b = 80- c
Now substitute that for b in the second equation:
2(80-c) + 4c = 270
Simplify:
160 - 2c + 4c = 270
160 +2c = 270
Subtract 160 from both sides:
2c = 110
Divide both sides by 2
c = 110/2
c = 55
Replace c with 55 in the first equation and solve for b:
b + 55 = 80
b = 80-55
b = 25
b = 25, c = 55
Give the equation for a circle with the given center and radius.
Center at (4, 1), radius = 6
Answer:
(x-4)^2 + (y-1)^2 = 6^2
or
(x-4)^2 + (y-1)^2 = 36
Step-by-step explanation:
The equation for a circle is given by
(x-h)^2 + (y-k)^2 = r^2
where (h,k) is the center and r is the radius
(x-4)^2 + (y-1)^2 = 6^2
or
(x-4)^2 + (y-1)^2 = 36
Answer:
(x - 4)^2 + (y - 1)^2 = 6^2
Step-by-step explanation:
Adapt the standard equation of a circle with center at (h, k) and radius r:
(x-h)^2 + (y-k)^2 = r^2
Here we have:
(x - 4)^2 + (y - 1)^2 = 6^2
i don't understand the problem
Check the picture below.
What is the factored form of 3x2 + 5x - 12?
Answer:
[x + 3][3x - 4]
Step-by-step explanation:
First off, we need to find two numbers that when differed to 5, they also multiply to -36 [3 × -12]. Those numbers are -4 and 9. Next, we find the Greatest Common Factor [GCF], which means the LEAST DEGREE TERM possible:
[3x² - 4x] + [9x - 12]
x[3x - 4] 3[3x - 4]
As you can see, whenever we have a leading coefficient greater than 1, we need to break up our B into our two numbers we found [in BOLD], and have to attach an x to them because it replaced Bx, according to the Quadratic Equation of y = Ax² + Bx + C. So, after we completed our factoring, you see two identical factors, which we use ONCE. The other factor comes from the terms outside the duplicates. So, you get the above answer after you completed the steps: [x + 3][3x - 4].
I am joyous to assist you anytime.
4 times the sun q and p
Typo is probably in "sun" being really "sum".
Just write an equation.
[tex]4(q+p)=4q+4p[/tex]
Hope this helps.
r3t40
Expected Value (50 points)
Game: Roll two dice. Win a prize based on the sum of the dice.
Cost of playing the game: $1
Prizes:
Win $10 if your sum is odd.
Win $5 if you roll a sum of 4 or 8.
Win $50 if you roll a sum of 2 or 12.
Answer both question. Will give brainly.
Explain HOW to find the expected value of playing this game. What is the expected value of playing this game? Show your work. (30 points)
Interpret the meaning of the expected value in the context of this game. Why should someone play or not play this game. Answer in complete sentences. (20 points)
Let [tex]W[/tex] be the random variable representing the winnings you get for playing the game. Then
[tex]W=\begin{cases}9&\text{if the sum is odd}\\4&\text{if the sum is 4 or 8}\\49&\text{if the sum is 2 or 12}\\-1&\text{otherwise}\end{cases}[/tex]
First thing to do is determine the probability of each of the above events. You roll two dice, which offers 6 * 6 = 36 possible outcomes. You find the probability of the above events by dividing the number of ways those events can occur by 36.
The sum is odd if one die is even and the other is odd. This can happen 2 * 3 * 3 = 18 ways. (3 ways to roll even with the first die, 3 ways to roll odd for the die, then multiply by 2 to count odd/even rolls)The sum is 4 if you roll (1, 3), (2, 2), or (3, 1), and the sum is 8 if you roll (2, 6), (3, 5), (4, 4), (5, 3), or (6, 2). 8 ways.The sum is 2 if you roll (1, 1), and the sum is 12 if you roll (6, 6). 2 ways.There are 36 total possible rolls, from which you subtract the 18 that yield a sum that is odd and the other 10 listed above, leaving 8 ways to win nothing.So the probability mass function for this game is
[tex]P(W=w)=\begin{cases}\frac12&\text{for }w=9\\\frac29&\text{for }w=4\text{ or }w=-1\\\frac1{18}&\text{for }w=49\\0&\text{otherwise}\end{cases}[/tex]
The expected value of playing the game is then
[tex]E[W]=\displaystyle\sum_ww\,P(W=w)=\frac{71}9[/tex]
or about $7.89.
The expected value is positive, so a player can expect to earn money in the long run, and so should play the game.
Please help!!!
Estimate the value of \sqrt(14)+\sqrt(3) to the nearest hundredth.
A. 3.79
B. 5.47
C. 2.01
D. 4.12
Answer:
B.
Step-by-step explanation:
Let's figure out what two consecutive integers is 14 between.
We also need to do this for 3.
14 is between 9 and 16 which means [tex]\sqrt{14}[/tex] is between [tex]\sqrt{9}[/tex] and [tex]\sqrt{16}[/tex].
3 is between 1 and 4 which means [tex]\sqrt{3}[/tex] is between [tex]\sqrt{1}[/tex] and [tex]\sqrt{4}[/tex].
So 14 is closer to 16 which means [tex]\sqrt{14}[/tex] is closer to 4. Let's say [tex]\sqrt{14}\approx 3.7[/tex]
So 3 is closer to 4 which means [tex]\sqrt{3}[/tex] is closer to 2. Let's say [tex]\sqrt{3}\approx 1.8[/tex].
So now we do 3.7+1.8=5.5.
The answer that is closet to this is 5.47.
Now if we put [tex]\sqrt{14}+\sqrt{3}[/tex] in our calculator we get:
3.74+1.73=5.47
4.4.45
For the following polynomial, one zero
is given. Find the remaining zeros.
The
(Sim
to se!
P(x) = x4 + 27x^2 - 324, 6i is a zero.
Answer:
[tex](x-6i)(x+6i)(x-3)(x+3)[/tex]
Step-by-step explanation:
If 6i is a zero then -6i is a zero.
In general, if a+bi is a zero then a-bi is a zero (if the polynomial has real coefficients which this one does: 1,27,-324).
Let's test it to see:
Check [tex]x=6i[/tex]
[tex]P(6i)=(6i)^4+27(6i)^2-324\\
P(6i)=6^4(i^4)+27(6)^2(i^2)-324\\
P(6i)=1296(1)+27(6^2)(-1)-324\\
P(6i)=1296-27(36)-324\\
P(6i)=1296-972-324\\
P(6i)=1296-1296\\
P(6i)=0\\[/tex]
Check [tex]x=-6i[/tex]
[tex]P(-6i)=(-6i)^4+27(-6i)^2-324\\
P(-6i)=(6i)^4+27(6i)^2-324\\
P(-6i)=P(6i)\\
P(-6i)=0\\[/tex]
So yep they both give us 0 when we plug it in.
If x=6i is a zero then x-6i is a factor by factor theorem.
If x=-6i is a zero then x+6i is a factor by factor theorem.
What is (x-6i)(x+6i)?
Let's use the multiply conjugates formula: [tex](u-v)(u+v)=u^2-v^2[/tex].
[tex](x-6i)(x+6i)=x^2-36i^2=x^2-36(-1)=x^2+36[/tex]
Now we know [tex](x^2+36)[/tex] is a factor of [tex]x^4+27x^2-324[/tex].
We can use long division or we could try to find two numbers that multiply to be -324 and add up to be 27 since this is a quadratic in terms of [tex]x^2[/tex] with leading coefficient of 1.
Well we already know we are looking for number times 36 that would give us -324.
So -324=-9(36) and 27=-9+36
So the factored form in terms of real numbers is:
[tex](x^2+36)(x^2-9)[/tex]
We already know the first factor can be factored as (x+6i)(x-6i).
The other can factored as (x-3)(x+3) since (-3)(3)=-9 and -3+3=0.
So the complete factored form is
[tex](x-6i)(x+6i)(x-3)(x+3)[/tex].
To find the remaining zeros of the polynomial, we use synthetic division and find a quadratic factor. The remaining zeros are the solutions to the quadratic equation x^2 + 9 = 0, which are 3i and -3i.
Explanation:To find the remaining zeros of the polynomial, we can use polynomial long division or synthetic division. Let's use synthetic division:
Since 6i is a zero of P(x), the conjugate -6i is also a zero. We can divide P(x) by (x - 6i)(x + 6i) to find the remaining quadratic factor.
Performing the synthetic division, we get a quadratic factor of x^2 + 9. Therefore, the remaining zeros of the polynomial are the solutions to the equation x^2 + 9 = 0.
Solving the quadratic equation x^2 + 9 = 0, we find that the remaining zeros are x = 3i and x = -3i.
Learn more about Polynomial zeros here:https://brainly.com/question/33963189
#SPJ11
25. Tom and Jerry must stuff and mail 1000
envelopes for a new marketing campaign. Jerry
can do the job alone in 6 hours. If Tom helps,
they can get the job done in 4 hours. How long
would it take Tom to do the job by himself?
A. 4 hours
B. 5 hours
C. 8 hours
D. 12 hours
Answer:
12
Step-by-step explanation:
The general formula for this is
Formula
1/t1 + 1/t2 = 1/t_tot
givens
t1 = 6 hours
t2 = x
t_tot = 4 hours
Solution
1/6 + 1/x = 1/4 Subtract 1/6 from both sides.
1/6-1/6 + 1/x = 1/4 - 1/6 Change to 12 as your common denominator
1/x = 3/12 - 2/12 subtract
1/x = 1/12 Cross multiply
x = 12
Tom would need 12 hours to do the job alone.
Answer:
Option D. 12 hours
Step-by-step explanation:
Let the work done by Tom to do the job alone = x hours
So per hour work done by Tom = [tex]\frac{1}{x}[/tex]
Jerry can do the job alone in the time = 6 hours
Per hour work done by Jerry = [tex]\frac{1}{6}[/tex]
Similarly job done by both together in the time = 4 hours
Per hour work done by both together = [tex]\frac{1}{4}[/tex]
Now we know,
Per hour work done by both together = per hour work done by Tom + Per hour work don by Jerry
[tex]\frac{1}{4}=\frac{1}{x}+\frac{1}{6}[/tex]
[tex]\frac{1}{x}=\frac{1}{4}-\frac{1}{6}[/tex]
[tex]\frac{1}{x}=\frac{3-2}{12}[/tex]
[tex]\frac{1}{x}=\frac{1}{12}[/tex]
x = 12 hours
Option D. will be the answer.
what is an inequality? where would u use them in the real world
An inequality is comparing the relation of two equations that are not equal.
Depending on a persons cell phone plan, if they can only talk for so many minutes per month or send so many texts per month, this is an inequality written as number of minutes/ texts per month needs to be less than or equal to the allowable amount.
La suma de las edades de unos gemelos y unos trillizos es 150 años si se intercambian las edades la nueva suma es 120 años ¿ cual es la edad de los trillizos?
Answer:
The age of triplets is 42 years old
Step-by-step explanation:
The question in English is
The sum of the ages of twins and triplets is 150 years if the ages are exchanged the new sum is 120 years. What is the age of triplets?
Let
x -----> twins age
y ----> triplets age
we know that
2x+3y=150 ------> equation A
2y+3x=120 -----> equation B
Solve the system by graphing
The intersection point both graphs is the solution of the system
The solution is the point (12,42)
see the attached figure
therefore
The age of triplets is 42 years old
1/8 x3-1/27y3 please help ...factor ths expression completely, then place the factors in the proper location on the grid
Answer:
factored form is: [tex](\frac{x}{2}-\frac{y}{3})(\frac{x^2}{4}+\frac{xy}{6}+\frac{y^2}{9})[/tex]
Step-by-step explanation:
The given expression is:
[tex]\frac{1}{8}x^3 - \frac{1}{27}y^3[/tex]
The expression can be written as:
[tex](\frac{1}{2}x)^3-(\frac{1}{3}y)^3[/tex]
We know, a^3-b^3 = (a-b)(a^2+ab+b^2)
a= x/2 and b = y/3
Putting values in the formula given:
[tex](\frac{x}{2}-\frac{y}{3})((\frac{x}{2})^2+(\frac{x}{2})(\frac{y}{3})+(\frac{y}{3})^2)\\(\frac{x}{2}-\frac{y}{3})(\frac{x^2}{4}+\frac{xy}{6}+\frac{y^2}{9})[/tex]
So, factored form is: [tex](\frac{x}{2}-\frac{y}{3})(\frac{x^2}{4}+\frac{xy}{6}+\frac{y^2}{9})[/tex]
Find x to the nearest tenth.
Please answer
Using the Pythagorean theorem:
x = √(11.7^2 - 8.6^2)
x = √(136.89 - 73.96)
x = √62.93
x = 7.9
The answer is D.
The function F(c) = 9/5 c + 32 allows you to
Answer:
convert from Celsius to Fahrenheit
Step-by-step explanation:
i work with thermometers i know
For this case we have that by definition, to convert degrees Celsius to Fahrenheit we use the following formula:
[tex]F = \frac {9} {5} C + 32[/tex]
Where:
C: Represents the degrees Celsius
So, we can write a function:
[tex]F (C) = \frac {9} {5} C + 32[/tex]
Answer:
The function allows to convert degrees Celsius to Fahrenheit
the point (3,0) lies on the graph of P(x)=x^3-7x^2+15x-9. True or False
Answer:
True
Step-by-step explanation:
We can plug in and see.
If (3,0) is on the graph of P, then P(3) will evaluate to 0.
Let's try it:
P(3)=(3)^3-7(3)^2+15(3)-9
P(3)=27-7(9)+45-9
P(3)=27-63+45-9
P(3)=-36+45-9
P(3)=9-9
P(3)=0
Since P(3)=0, then (3,0) is an ordered pair of P.
Yes it is true that the point (3,0) lies on the graph of
P(x) = [tex]x^{3}-7x^{2} +15x-9[/tex].
What is an equation?An equation is a mathematical statement with an 'equal to' symbol between two expressions that have equal values.
Given equation
P(x) = [tex]x^{3}-7x^{2} +15x-9[/tex]
If (3,0) is on the graph of P, then P(3) will evaluate to 0.
Substitute x = 3 in the given equation
P(3) = [tex](3)^3-7(3)^2+15(3)-9[/tex]
P(3) = [tex]27-7(9)+45-9[/tex]
P(3) = [tex]27-63+45-9[/tex]
P(3) = 9-9
P(3) = 0
Since P(3)=0, then (3,0) is an ordered pair of P.
Yes it is true that the point (3,0) lies on the graph of
P(x) = [tex]x^{3}-7x^{2} +15x-9[/tex].
Find out more information about equation here
brainly.com/question/2263981
#SPJ2
The Garcia family and the Lee family each used their sprinklers last summer. The Garcia family's sprinkler was used for 40 hours. The Lee family's sprinkler was used for 20 hours. There was a combined total output of 2000L of water. What was the water output rate for each sprinkler if the sum of the two rates was 60L per hour?
Answer:
Lee= 20 L per hour.
Garcia = 40L per hour
Step-by-step explanation:
This formula is:
40x + 20y = 2000L
with if being known that x + y = 60.
In this x is the rate for Garcia and y is the rate for Lee.
You can also say that x = 60 - y, which you can fill in.
40 * (60-y) + 20y = 2000
2400 - 40y + 20y = 2000
-20y = -400
y = 20 L per hour.
So x = 60 - 20 = 40L per hour
What are the sides of PQR?
Answer:
Hi there!
The answer to this question is: B
Answer choice B is correct because the dash above the two letter represents a line segment or side of a triangle
-------------------------------------------------------------------------------------------
Answer choice A: incorrect
Explanation: The little carrot in front of each letter shows that it is an angle not a side
Answer C: incorrect
Explanation: It tells you points of the triangle
Answer:
B.Step-by-step explanation:
[tex]A.\ \angle P,\ \angle Q,\ and\ \angle R-\bold{angles}\\\\B.\ \overline{PQ},\ \overline{QR},\ and\ \overline{PR}-\bold{sides}\\\\C.\ P,\ Q,\ and\ R-\bold{vertexs}[/tex]
y varies inversely with x. When y = 3.6, x = 1.2. What is the value of k, the constant of inverse variation? Round to the nearest hundredth, if necessary.
Answer:
The constant, k, is 4.32.
Step-by-step explanation:
y varies inversely with x means y=k/x.
y varies directly with x means y=kx.
Anyways we have the first relation: y=k/x where k is a constant.
We divided by x because it said inversely.
We are given (x,y)=(1.2,3.6) is on this curve.
This gives us enough information to find the constant, k.
[tex]y=\frac{k}{x}[/tex] with [tex](x,y)=(1.2,3.6)[/tex].
[tex]3.6=\frac{k}{1.2}[/tex]
Multiply both sides by 1.2:
[tex]3.6(1.2)=k[/tex]
[tex]4.32=k[/tex]
The constant, k, is 4.32.
Please help me.. What is the length of side x?
3.25
12
14.5
16
Answer:
x = 16
Step-by-step explanation:
Since the triangles are similar then the ratios of corresponding sides are equal, that is
[tex]\frac{RS}{MN}[/tex] = [tex]\frac{RT}{MO}[/tex], that is
[tex]\frac{8}{x}[/tex] = [tex]\frac{6.5}{13}[/tex] ( cross- multiply )
6.5x = 104 ( divide both sides by 6.5 )
x = 16
find an explicit formula for the arithmetic sequence -45,-30,-15,0...
Answer:
15(n-1)-45
Step-by-step explanation:
Increases by 15, so sequence is arithmetic, and goes to positive.
1st term is -45
so 15(n-1) gives us first term.
Reply for any questions I got you
[tex]\bf -45~~,~~\stackrel{-45+15}{-30}~~,~~\stackrel{-30+15}{-15}~~,~~\stackrel{-15+15}{0}~\hspace{7em}\stackrel{\textit{common difference}}{d=15} \\\\[-0.35em] ~\dotfill\\\\ n^{th}\textit{ term of an arithmetic sequence} \\\\ a_n=a_1+(n-1)d\qquad \begin{cases} a_n=n^{th}\ term\\ n=\textit{term position}\\ a_1=\textit{first term}\\ d=\textit{common difference}\\ \cline{1-1} a_1=-45\\ d=15 \end{cases} \\\\\\ a_n=-45+(n-1)15\implies a_n=-45+15n-15\implies a_n=15n-60[/tex]
Find the center and radius of the circle (x+3)^2+(y-1)^2=81
The equation of a circle is written as ( x-h)^2 + (y-k)^2 = r^2
h and k is the center point of the circle and r is the radius.
In the given equation (x+3)^2 + (y-1)^2 = 81
h = -3
k = 1
r^2 = 81
Take the square root of both sides:
r = 9
The center is (-3,1) and the radius is 9
In a triangle, the measure of the second angle is twice the measure of the first angle. the third angel is equal to the sum of the other angels
Answer:
So the angles have measurements 30,60, and 90 degrees.
Step-by-step explanation:
We have a triangle which means the interior angles of that triangle has sum 180 degrees.
Let's call the angle measurements: A, B, and C.
A+B+C=180
B=2A (The second angle is twice the first.)
C=A+B (The third angle is the sum of the other 2.)
If C=A+B, then C=A+2A (since B=2A).
So we have this system:
A+B+C=180
B=2A
C=3A (since C=A+2A=3a).
Now I'm going to use the first equation A+B+C=180 and plug in the other equations we have below it:
A+B+C=180 with B=2A and C=3A.
A+2A+3A=180
6A=180
Divide both sides by 6:
A=180/6
A=30
If B=2A and A=30, then B=2(30)=60.
If C=3A and A=30, then C=3(30)=90.
So the angles have measurements 30,60, and 90 degrees.
37. Two years ago, Bob flew 6 x 105 miles in an airplane. This was 15 times as many
miles as he flew last year.
How many miles did Bob fly last year?
A. 4* 104 miles
B. 4 x 106 miles
C. 9 x 104 miles
D. 9 * 106 miles
Answer:
A. 4·10⁴
Step-by-step explanation:
The problem statement tells you ...
6×10⁵ miles = 15 × (last year's mileage)
Dividing by 15 gives ...
(60×10⁴ miles)/15 = (last year's mileage) = 4×10⁴ miles
_____
Further explanation
An exponent is an indication of repeated multiplication.
10⁵ = 10·10·10·10·10 = 100,000
We can use the associative property of multiplication to rewrite the number of miles:
6×10⁵ = 6·(10·10·10·10·10) = 600,000 = (6·10)·(10·10·10·10) = 60×10⁴
You are choosing 3 of your 7 trophies and arranging them in a row on a shelf.
In how many different ways can you choose and arrange the trophies?
Answer:
21
Step-by-step explanation:
you can arrange 7×3 ways
Answer with explanation:
Number of trophies possessed by me= 7
Number of trophies that is to be selected from 7 trophies =3
⇒⇒So, Chosing 3 out of 7 trophies and arranging them on a shelf requires Concept of Permutation, as order of arrangement is also taken into consideration
[tex]=_{3}^{7}\textrm{P}\\\\=\frac{7!}{(7-3)!}\\\\=\frac{7!}{4!}\\\\=\frac{4!*5*6*7}{4!}\\\\=5*6*7\\\\=210\text{Ways}[/tex]
Or
⇒First place can be filled in 7 ways,second place can be filled in 6 ways and third place can be filled in 5 ways.
So total number of ways of selecting 3 trophies from 7 trophies
=7 *6 *5
=210 ways
⇒Now, 3 trophies can be arranged in a shelf in 3! =3 *2*1=6 ways.
Everyday there are 4 times more like on an internet video of a horse which is modeled by the function c(n)=(4)^n-1 where n is the number of day since the video posted on the first day there were 100 likes what is the function that shows the number of likes each day
Answer:
Step-by-step explanation:
A better way to write the first function would be:
c(n) = 4*c(n-1), meaning that the number of likes is equal to four times the number of likes from the previous day.
On the first day, c(n)=c(0) = 100
Therefore:
C(n) = 100 * 4^n
Let's plug in a view values to test our function:
When n= 0 (first day)
C(0) = 100 * 4 ^0 = 100*1 = 100 likes
C(1) = 100 * 4^1 = 100 * 4 = 400 likes, four times the previous day
C(2) = 100 * 4^2 = 100 * 16 = 1600 likes, four times the previous day
And so on. Our function is an accurate descriptor of the model.
What is the vertex of the graph of y = 5(x + 4)2 + 3? (1 point)
Answer:
[-4, 3]
Step-by-step explanation:
That -h gives you the OPPOSITE terms of what they really are, and k gives you the EXACT terms of what they really are. So, your vertex is [-4, 3].
If you are ever in need of assistance, do not hesitate to let me know by subscribing to my channel [USERNAME: MATHEMATICS WIZARD], and as always, I am joyous to assist anyone at any time.
Which of the sets of ordered pairs represents a function?
A = {(1, -2). (3.-5), (5,2), (7,5)}
B = {(4,2), (4, -2), (9,3), (9, -3)}
Answer:
The correct answer is A. Each x-value corresponds to exactly one y-value.
Solve the system of equation and choose the correct ordered pair.!2x-6y=8 5x-4y=31
Answer:
The correct ordered pair is (7,1)
Step-by-step explanation:
The given system has equations:
[tex]2x - 6y = 8....(1)[/tex]
[tex]5x- 4y = 31....(2)[/tex]
We make x the subject in the first equation to get:
[tex]x = 4 + 3y...(3)[/tex]
Put equation 3 into equation 2 to get:
[tex]5(4 + 3y) - 4y = 31[/tex]
Expand:
[tex]20 + 15y - 4y = 31[/tex]
[tex]15y - 4y = 31 - 20[/tex]
[tex]11y = 11[/tex]
[tex]y = 1[/tex]
Put y=1 into equation 3 and solve for x.
[tex]x = 4 + 3( 1) = 7[/tex]
The correct ordered pair is (7,1)